Problematika Pemenuhan Nafkah Anak Pasca Perceraian dalam Prespektif Lawrence Friedman - Wahyuni, Sri; Yuni, Lilik Andar (CV. Creative Tugu Pena, 2024)
This article discusses the execution of divorce decisions related to the fulfillment of child support after divorce, analyzed through the perspective of law enforcement according to Lawrence Friedman. The main focus is on how the legal system affects the implementation of child support obligations and the factors that influence its effectiveness. Using Friedman's three-element legal system theoretical framework—legal structure, substance, and culture—this article explores the obstacles and potential solutions in enforcing court decisions. The results of the analysis show that obstacles in the legal structure and community culture often hinder the implementation of child support obligations, even though the legal substance is adequate. Therefore, reforms in the legal system and increased public legal awareness are needed to ensure the welfare of children after divorce.